Rapid forgetting results from competition over time between items in visual working memory. - Pertzov, Y; Manohar, S; Husain, M (American Psychological Association, 2016)
Working memory is now established as a fundamental cognitive process across a range of species. Loss of information held in working memory has the potential to disrupt many aspects of cognitive function. However, despite its significance, the mechanisms underlying rapid forgetting remain unclear, with intense recent debate as to whether it is interference between stored items that leads to loss of information or simply temporal decay. Here we show that both factors are essential and interact in a highly specific manner. Although a single item can be maintained in memory with high fidelity, multiple items compete in working memory, progressively degrading each other's representations as time passes. Specifically, interaction between items is associated with both worsening precision and increased reporting errors of object features over time. Importantly, during the period of maintenance, although items are no longer visible, maintenance resources can be selectively redeployed to protect the probability to recall the correct feature and the precision with which cued items can be recalled, as if it was the only item in memory. These findings reveal that the biased competition concept could be applied not only to perceptual processes but also to active maintenance of working memory representations over time..